PERMASALAHAN PENERBITAN AKTA JUAL BELI DALAM KASUS NIRINA ZUBIR: The Problem Of Issuing A Deed Of Sale And Purchase In The Case Of Nirina Zubir - Nabil Listiawan; Dinda Keumala (Faculty of Law, Universitas Trisakti, 2025)
The legal act of transferring land rights through buying and selling according to Article 37 paragraph (1) of Government Regulation Number 24 of 1997 must have a deed made by the Land Deed Making Officer as proof that there has been a transfer of land rights from the seller to the buyer and the deed is needed for land registration. The problems discussed by researchers in this research are: what is the validity of the 6 (six) land sale and purchase deeds made in the presence of Ina Rosaina, S.H. and Erwin Riduan, S.Sos, S.H., M.Kn, Official Land Deed Maker in West Jakarta and what is the legal protection for the actual land owner for the land sale and purchase deed made in the presence of Ina Rosaina, S.H. and Erwin Riduan, S.Sos, S.H., M.Kn, Land Deed Making Officer in West Jakarta. The type of research used is normative research, the nature of the research is descriptive, the data used is qualitative analysis, the method of drawing conclusions used is deductive logic. The 6 (six) land sale and purchase deeds that were made were invalid, because they did not fulfill the characteristics of a sale and purchase according to the National Land Law and did not meet the requirements for making a land sale and purchase deed. The actual legal protection of land owners can be carried out in the form of repressive legal protection.